2014
DOI: 10.1039/c4ob00946k
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity in the nucleophilic aromatic substitution reactions of pyridinium ions

Abstract: The “element effect” in nucleophilic aromatic substitution reactions (SNAr) is characterized by the leaving group order, L = F > NO2 > Cl ≈ Br > I, in activated aryl substrates. A different leaving group order is observed in the substitution reactions of ring-substituted N-methylpyridinium compounds with piperidine in methanol: 2-CN ≥ 4-CN > 2-F ~ 2-Cl ~ 2-Br ~ 2-I. The reactions are second-order in [piperidine], the mechanism involving rate determining hydrogen-bond formation between piperidine and the substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…This perhaps could be due to increased effectiveness of radical grafting technique over microwave‐assisted radical grafting technique where the generated heat could have caused early decomposition of the reactants. Similarly, TC‐CNF had a higher phenolic content than TS‐CNF which is due to Cl groups being a better leaving group than tosylates in aromatic substitution reactions, thus resulted in increased grafting (Bowler et al., 2014). The esterification methods yielded significantly ( p < .05) better substitution for CNF compared to KC due to the insolubility of KC granules in the reaction solvent.…”
Section: Resultsmentioning
confidence: 99%
“…This perhaps could be due to increased effectiveness of radical grafting technique over microwave‐assisted radical grafting technique where the generated heat could have caused early decomposition of the reactants. Similarly, TC‐CNF had a higher phenolic content than TS‐CNF which is due to Cl groups being a better leaving group than tosylates in aromatic substitution reactions, thus resulted in increased grafting (Bowler et al., 2014). The esterification methods yielded significantly ( p < .05) better substitution for CNF compared to KC due to the insolubility of KC granules in the reaction solvent.…”
Section: Resultsmentioning
confidence: 99%
“…The CH 3 -rotation mechanism and the proton-transfer mechanism have also been proposed for X À + CH 3 Y -XCH 3 + Y À S N 2 gas-phase reactions, in which a pre-reaction complex and several other minimal structures could be located on their potential energy surfaces by DFT calculations. 13 For the S N Ar reactions, Wu et al have studied the mechanisms of piperidine with 2,4-dinitrophenyl substrates 9b or 2-substituted-N-methylpyridinium substrates 14 using HF/6-31+G (d) and MP2/6-31+G(d) models, and found that these S N Ar reactions proceed in the stepwise, addition-elimination mechanism, with the formation of an adduct intermediate being rate-determining. For the nucleophilic acyl substitutions, those involving butane-2,3-dione monoximates or p-chlorophenoxides as nucleophiles have been investigated extensively, and the additionelimination pathway was suggested to be prevalent in these systems.…”
Section: Introductionmentioning
confidence: 99%
“…12,15 Apart from reaction mechanisms, the structure-reactivity relationship has always been a hot topic for SN reactions. [6][7][8][9][10][11][12][13][14][15][16][17][18][19] Considering that most of these reactions are performed in solution, multiple factors, including the modulation of solvent and substitution on either the substrate or the nucleophile, may vary the overall reaction rates in a wide range. Plenty of experimental kinetic studies on SN reactions are also available in the literature, [7][8][9][10][11][12]19 and in this respect, activation entropy, activation enthalpy, activation free-energy and the reaction rate constant are most useful and indispensable kinetic parameters for quantitatively describing the reactivity, the reaction mechanism and the solvent effect.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the chlorinated counterpart, the o -fluoropyridinium cation exhibits about 100-fold higher reactivity, highlighting the special ability of the polarized C–F bond to promote S N Ar reactions . Alternatively, the p - and o -cyano- N -methylpyridinium cations exhibit 30 and 50-fold higher reactivity toward piperidine in methanol, respectively, compared to the o -fluoropyridinium moiety . Despite the promise of these electrophilic scaffolds for cysteine bioconjugation, the o -fluoropyridinium cation is a safer reagent that does not generate unwanted cyanide byproduct.…”
Section: Resultsmentioning
confidence: 99%